PENGEMBANGAN LKPD BERBASIS MEDIA WORDWALL MENGGUNAKAN MODEL PROBLEM BASED LEARNING PADA PEMBELAJARAN IPAS DI KELAS V SEKOLAH DASAR - Lubis, Mhd Yusril Aswandi; Yeni Erita; Arwin; Masniladevi; M. Habibi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low utilization of interactive and engaging technology-based learning media in elementary schools, particularly in the subject of Natural and Social Sciences (IPAS). The aim of this study is to develop a Wordwall-based Student Worksheet (LKPD) for the topic of Biodiversity for Grade V students in elementary school. The development of this LKPD employed the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The worksheet was designed to be engaging and interactive by utilizing various features available in the Wordwall application, thereby increasing students’ motivation, involvement, and comprehension during the learning process. The validity of the LKPD was tested by three experts: subject matter expert, language expert, and media expert. The validation results showed that the LKPD received a score of 97.5% from the subject matter expert, 95% from the language expert, and 95% from the media expert. The overall average validation score was 95.8%, which falls under the “valid” category. These results indicate that the developed Wordwall-based LKPD meets the feasibility standards and is suitable for use in classroom learning. Therefore, this developed product is considered appropriate for further field trials and has the potential to serve as an innovative, enjoyable, easily accessible learning media alternative that aligns with students’ learning needs in the evolving digital era.